Developing Thematic Subject Specific Pedagogy (SSP) to Improve Affective Domain of The Students in Grade 4 State Elementary School 1 Potrobangsan Magelang - Wulan Tri Puji Utami (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to produce a thematic Subject Specific Pedagogy (SSP) and test the effectiveness of the thematic SSP to improve the affective domain in grade IV elementary school students in Potrobangsan 1 Elementary School Magelang. This research is a Research and Development, which stages consist of: research and data collection; planning; development of product drafts; initial field trials; revision of trial results; field trials; improvement of field trial product products; field implementation test, improvement of the final product. Data collection instruments consisted of interview guidelines, product assessment sheets, SSP assessments by teachers, student observation sheets, response questionnaires and students. The results of this study are in the form of SSP which includes: syllabus, lesson plans, LKPD and evaluation sheets. The results of the SSP assessment are in the form of syllabus, lesson plans, LKPD and assessment sheets developed in good category. Thus it can be stated that the developed SSP was feasible and effective to improve the affective domain of grade IV primary school students.